Pembangunan Sistem Informasi Pengelolaan Klinik Mahardika berbasis Web - Yulianus Wayan Yudistira Rudja; Denny Sagita Rusdianto; Edy Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Mahardika Clinic is one of the primary clinics operating in the city of Bogor which provides pharmacy integrated with the clinic. The problem faced by the Mahardika Clinic is that the bookkeeping of medicines is asynchronous because when there is a sale of drugs, the Mahardika Clinic employees in charge of the pharmacy do not always update Excel because of the large number of patients served and another problem faced is drugs that are expired but unknown by clinic staff because there is no marker indicating that the drug in Excel will expire. From this problem, the solution provided by researchers in increasing the effectiveness of bookkeeping drug sales is to make notes that are integrated with the prescriptions given by doctors in the medical record, make drug accounting records that show drugs that will expire. From the solutions provided, the researchers developed these web-based solutions and used the waterfall method. The method begins with interviews, literature studies, needs analysis, design and implementation, testing, conclusions and suggestions. From the results of the needs analysis, there are 27 functional requirements and 1 non-functional requirement. the design and implementation results use the PHP programming language using the Laravel framework, MySQL. In unit testing, 3 samples were used which resulted in valid values and had a complexity value below 5 in all three samples, validation tests were carried out on 27 functional requirements which resulted in 100% valid values for 27 functional requirements, and compatibility testing was tested on 6 different browsers which provided result that the system runs fine across browsers.